Optimasi Load Frequency Control (LFC) Pada Sistem Pembangkit Listrik Tenaga Mikro Hidro Berbasis PID-ANFIS - Andrik, Mochamad; Farul, Mohamad; Cahyono, Iwan; Rukslin, Rukslin (Jurnal Rekayasa Mesin, 2018)
Microhydro Power Plant is a small-scale power plant.Microhydro plants are built in areas where there is no power grid.In areas with sufficient water potential to generate electrical energy.The problem that often occurs in the micro-hydro generator system is the occurrence of non-constant generator.This is caused by changes in connected loads.Thus causing frequent fluctuations in the frequency of the system that can cause damage to electrical equipment.Therefore used Load Frequency Control (LFC) in order to control the frequency can be more stable.To get the optimal control parameter in micro hydro power plant system is used an Artificial Intelligence (AI) that is Adaptive Neuro Fuzzy Inference System (ANFIS) method. ANFIS data is taken from PID controller training data.By using PID-ANFIS control method, microhydro generating system can accelerate settling time and minimize overshoot.